Unilateral hemichorea and hemiballismus: Rare complications of non-ketotic hyperglycemia - Hardil Paresh Majmudar,; Roy Ashok Mali, (Indian Journal of Case Reports, 2020)
Hemichorea-hemiballismus is an extremely rare and dramatic complication of non-ketotic hyperglycemia in patients with uncontrolled diabetes mellitus. Here, we present the case of a 65-year-old male, known hypertensive, diabetic with the left eye retinopathy who presented with the chief complaints of sudden onset hemichorea and hemiballismus on the right upper and lower limbs. Magnetic resonance imaging brain reported T1 hyperintense and T2 isointense/hypointense signal in the left putamen with no restricted diffusion – these signal changes. He was started on oral antihyperglycemics and a combination of tetrabenazine, clonazepam, and haloperidol. Mild resolution of symptoms was seen and the patient is on follow-up with advice to control sugar through diet and regular sugar monitoring.